41.9k views
4 votes
I need help ASAP thank you

I need help ASAP thank you-example-1

1 Answer

5 votes

Answer:

√9 × √6

√54

√27 × √2

Explanation:

We can obtain the answer to the question given above as illustrated below:

3√6

Recall

a√b = √(a×a×b)

Thus,

3√6 = √(3×3×6)

3√6 = √(9 × 6)

Recall

√(a × b) = √a × √b

√(9 × 6) = √9 × √6

Therefore,

3√6 = √9 × √6

Recall

√9 × √6 = √(9 × 6)

√9 × √6 = √54

Thus,

3√6 = √54

Recall

√54 = √(27 × 2)

√54 = √27 × √2

Therefore,

3√6 = √27 × √2

Therefore,

3√6 = √9 × √6 = √54 = √27 × √2

User Elmer Thomas
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.